Climatology of the migrating terdiurnal tide (TW3) in SABER/TIMED temperatures. Issue 4 (11th April 2013) - Pancheva, D.; Mukhtarov, P.; Smith, A. K.
Abstract : [1] The present paper is focused on the global spatial (altitude and latitude) structure and seasonal and interannual temporal variability of the migrating terdiurnal tide (TW3) seen in 8 years (2002–2009) of observations of the kinetic temperature measured by the SABER instrument on the TIMED satellite. The tides (migrating and nonmigrating) and the planetary waves (zonally traveling and stationary) are simultaneously extracted from the satellite data. It is found that the SABER TW3 tide is dominated by different Hough modes below and above 80 to 90 km height; in the mesosphere, it reflects mainly the evanescent feature of the first symmetric mode, and in the lower thermosphere, propagating modes with shorter vertical wavelengths dominate its structure. The seasonal behavior of the terdiurnal tide at low latitudes is dominated by an annual variation with local summer amplification, while that at midlatitudes is a combination of semiannual variation with maxima in equinoxes and an annual variability with winter enhancement. The Hough modes of the solar heating from WACCM heating to a large extent determine the predominantly antisymmetric features of the SABER TW3 tide during the solstice but are not able to explain well the predominant symmetric features in the equinoxes. The TW3 tide reveals some interannual variability with a period of quasi‐2 years which indicates an enhancement during the eastward phase of the stratospheric QBO. Key Points: SABER temperatures are used for defining the TW3 features TW3 reveals antisymmetric structure in solstice and symmetric in equinoxes Hough modes of heating determines antisymmetric TW3 features